PENYIDIKAN TINDAK PIDANA PENCURIAN BUAH KELAPA SAWIT DI WILAYAH HUKUM POLSEK SANGIR JUJUAN - Abu Dawar, Nurlinda Yenti dan (Normative Jurnal Ilmiah Hukum, 2023)
The theft of palm fruit that occurred in the jurisdiction of the Sangir Jujuan Police greatly disturbed public security and order. The crime of theft of oil palm fruit is a problem that is very detrimental to many parties, including plantation owners. The formulation of the problem in this study is how is the investigation into the crime of theft of palm fruit in the jurisdiction of the Sangir Jujuan Police? What are the obstacles in the investigation of the crime of theft of palm fruit in the jurisdiction of the Sangir Jujuan Police? What are the efforts to overcome obstacles in the investigation of the crime of theft of palm fruit at the Sangir Jujuan Police? The approach in this research is a sociological juridical approach. The results of the investigation into the crime of theft of palm fruit at the Sangir Jujuan Police on Police Report Number: Lp/13/V/2021/Spkt Polsek are receiving reports, taking the first action by establishing a police line at the TKP, arrest and detention, confiscation, taking fingerprints finger and photographing the suspect, examining the suspect and witnesses and submitting the Minutes of Examination to the Public Prosecutor. 4 of the Criminal Code. Obstacles in Investigating the Crime of Oil Palm Fruit Theft at the Sangir Jujuan Police in the Police Report Number: Lp/13/V/2021/Spkt Polsek are the factors of a lack of investigators at the Sangir Jujuan Police, transportation facilities, and the lack of food costs for prisoners. Efforts to Overcome obstacles in the investigation of the crime of theft of palm fruit at the Sangir Jujuan Police In the Police Report Number: LP/13/V/2021/SPKT Polsek is the addition of human resources in the Sangir Jujuan Sector Police, the addition of Transportation Facilities and charging food money to reporter